(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
A mixture of phosphorus pesticides was detected in different areas of the surrounding soils of Al Basil Dam in Safita, where the concentrations were ng/g and the highest concentrations were recorded near the mouth of the Alabrash River in the dam and the total value of Organophosphorus pesticides was 724.23ng/g, in the area of Sheikh Younis has reached The total concentration of these pesticides is 497.94 ng/g while the lowest concentrations are recorded in the region of the Yazidi 403. 1ng/g and the Sisenia area, which reached 172.28 ng/g, were the least contaminated by these pollutants, and the detected compounds were Phosdrin, Diazinon, Dichlorvos, malathion, Methyl parathion compound was detected near the mouth of the river Abrash in the dam and area near the house of Sheikh Younis and which prevented from use due to its risk and carcinogenic effect for man especially in an area